The LGBT files: the diverse truth is out there - Schoenmaekers, David; De Roover, Dennis; Wasserbauer, Marion (Zizo : magazine voor holebi's & transgenders)
"David Schoenmaekers; Dennis De Roover; Marion Wasserbauer Fonds Suzan Daniel (FSD)"